The Abduction - Gimenez, Mark. Gimenez, Mark. (New York : Vanguard Press, 2007)
"Ben Brice lives alone in the New Mexico wilderness where he battles memories of Vietnam with oceans of Jim Bean. Miles away in Texas, his estranged son, John, an internet geek-turned-billionaire, half watches his daughter Gracies soccer game while conducting business on his cell phone. When her mother Elizabeth arrives, the coach reports that her uncle has already collected Gracie. But Gracie has no uncle -- she was kidnapped." --from container.
Keywords: Kidnapping -- Fiction; Parent and child -- Fiction; Fathers and sons -- Fiction; Fiction